Pengaruh Terapi AIUEO terhadap Kemampuan Bicara Pasien Stroke yang Mengalami Afasia Motorik - Afnijar Wahyu; Liza Wati; Murad Fajri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the effect of AIUEO therapy on the speech ability of stroke patients who have motor aphasia in Raja Ahmad Thabib Hospital Tanjungpinang. The research design used was quasi experiment with the Nonequivalent Control Group Design approach. The results showed that there were significant differences in the functional ability of communication between the control and treatment groups with a value of p <0.05 (p = 0.007 at a = 0.05) using the Wilcoxon Test statistical test. Conclusion, the influence of AIUEO therapy on the speech ability of stroke patients with motor aphasia in the treatment and control groups at Ahmad Thabib Hospital Tanjungpinang. Keywords: Speech Ability, Motor Aphasia Stroke, AIUEO Therapy